2018
DOI: 10.3390/v10110642
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Exposure of Macaca fascicularis to Low Doses of Low Passage- or Cell Culture-Adapted Sudan Virus or Ebola Virus

Abstract: The filoviruses Ebola virus (EBOV) and Sudan virus (SUDV) can cause severe diseases, and there are currently no licensed countermeasures available for use against them. Transmission occurs frequently via contact with bodily fluids from infected individuals. However, it can be difficult to determine when or how someone became infected, or the quantity of infectious virus to which they were exposed. Evidence suggests the infectious dose is low, but the majority of published studies use high exposure doses. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Alfson et al demonstrated that a target dose of 1.0 × 10 −2 of wild-type EBOV administered via i.m. injection was fully lethal in cynomolgus macaques [ 59 ]. This suggests that while plaques at not detectable in a cell culture the inoculum still contains infectious virus particles able to cause disease.…”
Section: Discussionmentioning
confidence: 99%
“…Alfson et al demonstrated that a target dose of 1.0 × 10 −2 of wild-type EBOV administered via i.m. injection was fully lethal in cynomolgus macaques [ 59 ]. This suggests that while plaques at not detectable in a cell culture the inoculum still contains infectious virus particles able to cause disease.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SUDV, BDBV, TAFV, and RESTV challenges do not cause uniform lethality in cynomolgus macaques, and the median time to death in macaques infected these viruses appears to be longer than EBOV infection; SUDV causes 50-100% lethality in 9-10 d after infection with a dose of 10 3 PFU [6,137,139], BDBV causes 50-75% lethality in 10-13 d after infection with a dose of 10 3 − 10 4 TCID 50 or 10 3 PFU [141][142][143], TAFV causes 60% lethality in 10-14 d after infection with a dose of >10 3 PFU [139,144], and RESTV causes 80-100% lethality in 8-21 d after infection with a dose of 10 3 PFU [6,145]. Considering the fact that a lethal infection in macaques can be achieved by EBOV infection with challenge doses lower than 10 3 PFU -as low as 0.01 PFU or as little as one infectious unit -with various inoculation routes [146][147][148][149], SUDV, BDBV, TAFV, and RESTV seem to be inherently less virulent than EBOV in macaques. Parenthetically, RESTV seems to be a quite unique virus among ebolaviruses and is presumably an animal pathogen given its distinct virulence in macaques and humans.…”
Section: Disease Courses and Fatalities In Animal Modelsmentioning
confidence: 99%
“…Better datasets, such as those that could be collected through natural history studies, would help inform changes in blood chemistry parameters that may be predictive of lethal disease and/or serve as early biomarkers for euthanasia decisions. Such an approach was employed for assessment of the Ebola virus rhesus macaque model, which led to several institutions adopting secondary endpoints of temperature change and specific clinical chemistry values [ 78 , 79 ].…”
Section: Refinement Opportunitiesmentioning
confidence: 99%